Pattern of paediatric ear, nose and throat disorders in a district hospital - Gupta, Vijay; Gupta, Arindam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: ENT disorders such as otitis media, serous otitis media, sinusitis, and tonsillitis are among the commonest childhood disorders and important reasons for parents and children to visit the physicians/otolaryngologists. The pattern of ENT disorders also varies from community to community or hospital to hospital based on the availability of specialist personnel or facilities for the management. Present study was carried out with the objective of to study the pattern of paediatric ENT disorders in our Government district hospital. Methods: The patients of both gender and age between 0 to 16 years and presenting with ENT problems were screened. The patients having END disorders diagnosed by ENT surgeon were enrolled into the study. All information to accomplish objectives was collected by studying the patients’ treatment record and by personal interview of each of the study participants/parents for 5 to 10 minutes using case record form. Results: Children from rural community were more affected than children from urban community. The maximum children were suffered from ear disorders (49.32%) followed by throat disorders (34.55%); and nose disorders (16.14%). CSOM found the commonest ENT disorder, OME, AOM, tonsillitis, adenoid hypertrophy, and acute pharyngitis. In 0-5 years-age-group, AOM and OME were the commonest; CSOM and OME in 5-10 years age group while acute pharyngitis and CSOM were the commonest in age-group of 10-16 years. Conclusions: These results of the present study clearly show the wide prevalence of ENT disorders, particularly in the rural communities. There is urgent need to establish better healthcare especially ENT services for the rural population of our country. The general physicians and paediatricians should be trained and taught enough recognize common ENT disorders promptly; therefore they are able to refer early and prevent complication.